Comparison between 4 minutes and 8 minutes of resting interval on sprinting performance among adolescent athletes / Muhammad Nasrullah Nazri - Nazri, Muhammad Nasrullah (Faculty of Sport Science and Recreation, 2019)
The purpose of this study is to compare the differences between 4 minutes of rest interval and 8 minutes of resting interval on sprinting performance among adolescent athletes. A total of thirteen subjects (N=13) of Selangor Sports School athletic athletes was selected through purposive sampling. This study compared the differences between 4 minutes and 8 minutes of rest interval on sprinting performances. On the first day session, all of the subjects performed the plyometric (Post-activation Potentiation) exercise which is the athletes performed 3 sets of 10 alternate-leg bounds (5 contacts per leg per set), with 25 seconds each set recovery time with 4 minutes of rest interval after completed the 3 sets. The 30 meter sprint time was measured with a handheld stopwatch immediately after 4 minutes of the rest interval. On the second day session of this study, the same method was used for 8 minutes of rest interval on sprinting performance. Paired Sample T-test was used to analyze the data between 4 minutes and 8 minutes of rest interval on sprinting performance. The hypothesis was significant differences between 4 minutes and 8 minutes of rest interval after Post Activation Potentiation activities on sprinting performance (M=0.08, sd=0.03). The overall result also indicated that 4 minutes of rest interval on sprinting (M=4.22, sd = 0.10) was better than 8 minutes of rest interval on sprinting (M=4.31, sd = 0.11). Hence, from this study, the result can conclude 4 minutes of rest interval has been associated with better muscular explosives and helps in improving the sprinting performance.